Systematic Literature Review of Teacher-Based Applied Behavior Analysis (ABA) Strategies to Improve Eye Contact in Children with Autism in School Syahida Harapan Bunda - Ratih Darmastuti; Sri Susilogati Sumarti; Tri Joko Raharjo; Sri Sumartiningsih (Journal of Educational Sciences, 2026)
This study aims to systematically examine teacher strategies based on Applied Behavior Analysis (ABA) to enhance eye contact skills in children with Autism Spectrum Disorder (ASD) during classroom learning. A Systematic Literature Review (SLR) was conducted by analyzing ten empirical research articles published between 2020 and 2025. The review focused on structured learning approaches, teacher interventions, and the impact on visual attention and social engagement in autistic children. Findings indicate that eye contact does not occur spontaneously but develops through sequential behavioral stages, including compliance with instructions, emergence of visual attention, social responses, and functional eye contact. Teachers implement strategies such as gradual prompting, consistent positive reinforcement, use of visual media, and the Discrete Trial Training (DTT) approach to systematically guide children in achieving sustained eye contact during learning interactions. These interventions not only improve visual attention but also facilitate basic social communication skills. Across all studies reviewed, consistent application of ABA-based strategies by teachers significantly enhances the frequency and duration of eye contact, forming a foundation for social engagement and classroom participation. This review provides evidence-based guidance for educators in designing and implementing ABA strategies in school settings, highlighting the importance of structured, gradual, and reinforced teaching methods to support the social and academic development of children with ASD.